My geisha [videorecording (DVD)] - Parker, Steve; Cardiff, Jack; Krasna, Norman; MacLaine, Shirley, 1934-; Montand, Yves, 1921-1991; Robinson, Edward G., 1893-1973; Cummings, Robert, 1908-1990 (Archive collection., 2013)
An American actress disguises herself as a geisha and tries to convince her husband-director that she is right for the part in his film version of Madame Butterfly.